Teoría sistémica y los derechos de la naturaleza: Sentencia n.º 22-18-IN/21 (Tema Central) - Guerrero Bustillos, Katherin Paola (2024)
This paper shows a vision of the rights of nature from the postulates of the systemic theory, which provides parameters that must be taken at the time of analyze the article 71 of the Constitution of the Republic. The judgment n.º 22-18-IN/21 is an important precedent in the protection of the rights of Nature, not only for the recognition of these to a specific ecosystem, but also for the application of a theory that allows understanding the scope of the constitutional norm and its relevance for the protection of an ecosystem, in this case, the mangrove. For the development of this work, a qualitative methodology was applied through the search for information in national and international bibliographic, legal and jurisprudential sources. The result achieved consists in the identification of concepts that allow an in-depth analysis of the scope of the rights of nature and their application in specific cases. Consequently, the judgment n.º 22-18-IN/21 is a reference for the protection of the rights of nature, setting standards that must be observed in a decision, and the Constitutional Court and the Ordinary Justice have considered in subsequent judgments.